Water injection in single well model case study: Injeksi air dalam studi kasus model sumur tunggal - Jihad Al-Joumaa; Karrar Karem Saddam; Muhammad Ali Hammood; Mustafa Mohammed Fadhil (Universitas Muhammadiyah Sidoarjo, 2024)
This study compares two water injection patterns (line drive and five-spot) using CMG software in a cubic reservoir model based on Buzergan field data. Line drive injection showed higher water cut rates due to direct water flow, while the five-spot pattern distributes water flow across the area, resulting in lower water cuts. Economic analysis favors the line drive pattern for its lower setup cost and reduced water injection requirements. These findings offer insights for optimizing injection patterns and maximizing oil production in reservoir management. Highligt: Injection Pattern Comparison: Direct vs. Distributed Water Flow Analysis. CMG Software Simulation: Accurate Reservoir Modeling and Analysis Tool. Cost-Effective Optimization: Maximizing Oil Production with Economical Injection Strategies. Keyword: Water Injection Patterns, CMG Software, Reservoir Management, Oil Production Optimization, Economic Analysis